Difference of Intrahost Dynamics of the Second Human Pegivirus and Hepatitis C Virus in HPgV-2/HCV-Coinfected Patients - Liang, Yuanhao; Hu, Fengyu; Fan, Hang; Li, Linghua; Wan, Zhengwei; Wang, Haiying; Shui, Jingwei; Zhou, Yuanping; Tong, Yigang; Cai, Weiping; Tang, Shixing (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The second human pegivirus (HPgV-2) and hepatitis C virus (HCV) belong to the Flaviviridae family and share some common genome features. However, the two viruses exhibit significant genetic diversity. The comparison of intra-host dynamics of HPgV-2 and HCV that mainly reflect virus-host interactions is needed to elucidate their difference of genetic diversity and the possible mechanisms. Methods: Intra-host single nucleotide variations (iSNVs) were identified by means of next-generation sequencing from both cross sectional and longitudinal samples from HPgV-2 and HCV co-infected patients. The levels of human cytokines are quantified in the patient before and after HCV elimination by the treatment of direct acting antivirals (DAA). Results: Unlike HCV, the viral sequences of HPgV-2 are highly conserved among HPgV-2 infected patients. However, iSNV analysis confirmed the intra-host variation or quasispecies of HPgV-2. Almost all iSNVs of HPgV-2 did not accumulate or transmit within host over time, which may explain the highly conserved HPgV-2 consensus sequence. Intra-host variation of HPgV-2 mainly causes nucleotide transition in particular at the 3rd codon position and synonymous substitutions, indicating purifying and negative selection posed by host immune system. Cytokine data further indicate that HPgV-2 infection alone may not efficiently stimulate innate immune responses since pro-inflammatory cytokines expression dramatically decreased with elimination of HCV. Conclusion: This study provided us new insights into the intra-host genomic variations and evolutionary dynamics of HPgV-2 as well as the impact of host immune selection and virus polymerase on virus evolution. The major difference of HPgV-2 and HCV makes HPgV-2 a new model to investigate RNA virus diversity and the mechanism of HPgV-2 polymerase in modulating virus replication.